Disease due to Mycobacterium kansasii in the Czech Republic: 1984-89 - Kaustová, J; Chmelík, M; Ettlová, D; Hudec, V; Lazarová, H; Richtrová, S (Tubercle and lung disease, 1995)
SETTING: Endemic area of North Moravia, Czech Republic. OBJECTIVE: Evaluate the incidence of human disease due to Mycobacterium kansasii. The follow-up of some bacteriological and clinical features. DESIGN: A retrospective analysis of M. kansasii patients. RESULTS: M. kansasii was isolated from the sputum, tissue and other specimens obtained from 650 persons during the period 1984-89. In only 471 of them was this mycobacterium deemed to be the causative agent, predominantly of lung disease. The most typical radiographic finding in these patients was lung infiltration and/or thin-walled cavity. CONCLUSION: As in previous years the highest incidence of disease remains in an endemic area of North Moravia. The effects of treatment in follow-up patients were influenced not only by the antituberculosis regimen but also by a high frequency of associated diseases. Sputum conversion within 30 days was not affected by the presence or absence of a cavity. Authors consider water to be the source of infection.
Keywords: Rifampin; atypické mykobakteriální infekce; netuberkulózní mykobakterie; Female; antituberkulotika; plicní tuberkulóza; Tuberculosis, Pulmonary; ženské pohlaví; rifampin; lidé; Drug Resistance, Microbial; Anti-Bacterial Agents; Mycobacterium Infections, Nontuberculous; retrospektivní studie; Male; Czech Republic; Nontuberculous Mycobacteria; kombinovaná farmakoterapie; Česká republika; lidé středního věku; Antitubercular Agents; mužské pohlaví; antibakteriální látky; Retrospective Studies; Middle Aged; antibiotická rezistence; Drug Therapy, Combination; Humans